The co-pollutant cost of carbon emissions: an analysis of the US electric power generation sector. (20th August 2019) - Dedoussi, Irene C; Allroggen, Florian; Flanagan, Robert; Hansen, Tyler; Taylor, Brandon; Barrett, Steven R H; Boyce, James K
Abstract: Fossil fuel combustion releases carbon dioxide into the atmosphere along with co-pollutants such as sulfur dioxide, nitrogen oxides, and others. These emissions result in environmental externalities primarily in terms of climate and air quality. Here we quantify the cost of co-pollutant emissions per ton of CO2 emissions from US electric power generation. We measure the co-pollutant cost of carbon (CPCC) as the total value of statistical life associated with US-based premature mortalities attributable to co-pollutant emissions, per mass of CO2 . We find an average CPCC of ∼45 per metric ton (mt) of CO2 for the year 2011 (in 2017 USD). This is ∼20% higher than the central Social Cost of Carbon (SCC) measure of climate damages that was used by the Obama administration in its regulatory impact analysis for the Clean Power Plan (CPP), and >8 times higher than the SCC used by the Trump administration in its analysis for the Plan's repeal. At the state-level, the CPCC ranged from ∼7/mt CO2 for Arizona to ∼96/mt CO2 for New Jersey. We calculate the CPCC trends from 2002 to 2017 and find a 71% decrease at the national level, contributing to total savings of ∼1 trillion in averted mortality from power plant emissions over this period. By decomposing the aggregate and fuel-specific co-pollutant intensities into simultaneous (CO2 -driven) and autonomous components, we conclude that the CPCC trends originated mainly from targeted efforts to reduce co-pollutant emissions, e.g. through fuel switching (from coal to natural gas) and autonomous changes in co-pollutant emissions. The results suggest that the overall benefit to society from policies to curtail carbon emissions may be enhanced by focusing on pollution sources where the associated air-quality co-benefits are greatest. At the same time, continued efforts to reduce co-pollutant intensities, if technologically feasible, could help to mitigate the air-quality damages of the CPP's repeal and replacement.